The emergence and interpretation of project orientation and project thinking as a competence in secondary education - Csiszárik-Kocsir, Ágnes; Berényi, Csaba (Vezetéstudomány / Budapest Management Review, 2025)
In the rapidly changing world, it has become fashionable to organize and interpret activities as projects: activities that produce a unique, unrepeatable, one-off result and do so under specific boundary conditions. Education in project thinking should start at a very early age, so it is worth starting in the upper primary school years, but secondary education is also a very good setting for developing this skill. Project thinking as a core competence can be taught in various ways at different levels of education. PBL, CBL, and LBL-based teaching methods can be used in combination to develop this skill, along with all its attendant factors, in young people. It is vital that today’s education system recognizes the need for project thinking and project-based education. This study aims to investigate the perceptions and aptitude of secondary school students to think in projects and to work in teams within a defined framework.